Cutaneous Mucormycosis - Erlinda Karyadi; Leoni Agnes (PT Kalbe Farma Tbk., 2022)
Cutaneous mucormycosis is an emerging fungal infection caused by opportunistic fungi from phylum Glomeromycota. This disease is frequently found in poorly controlled diabetic patients and immunosuppressed individuals. It is usually acquired by direct inoculation through trauma. The clinical presentation is nonspecific indurated plaque rapidly evolves to necrosis. Diagnosis should be confirmed by demonstration of the etiological agent and molecular tests. First-line therapy is amphotericin B combined with surgery; second line treatment include posaconazole and isavuconazole. Cutaneous mucormycosis adalah infeksi jamur oportunistik dari filum Glomerycota. Penyakit ini sering dijumpai pada pasien diabetes tidak terkontrol serta pada pasien imunosupresi. Penyebaran penyakit ini umumnya inokulasi langsung melalui trauma. Gambaran klinis berupa plak berindurasi nonspesifik yang berkembang cepat menjadi nekrosis. Diagnosis melalui pemeriksaan kultur dan sejumlah tes molekular. Terapi lini pertama yaitu amphotericin B dengan pembedahan, lini kedua dapat menggunakan posaconazole dan isavuconazole.